Revisiting the ACP-EU economic partnership agreements: The role of complementary trade and investment policies - Matthias Busse (Intereconomics, 2010)
Negotiations on the Economic Partnership Agreements between African, Caribbean and Pacific countries and the European Union have not been making much progress recently. How should the Partnership Agreements be structured to ensure a pro-development outcome and how could the negotiations gain more momentum in the months and years ahead?
Keywords: 330